KNOWLEDGE ABSORPTIVE CAPACITY AND INNOVATION READINESS IN MSMES: AN INTEGRATIVE FRAMEWORK - Nyoman Dwika Ayu Amrita; Wawan Ichwanudin (Organisasi Kreatif Indonesia Emas, 2024)
This conceptual paper develops an integrative framework for knowledge absorptive capacity in micro, small, and medium enterprises (MSMEs). Drawing on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, resilience, and entrepreneurial-ecosystem literature, the paper explains how knowledge acquisition, assimilation, transformation, exploitation, and innovation readiness can be organized into practical managerial routines. No primary survey, interview, experimental, or statistical data are claimed. The analysis proposes a staged cycle of diagnosis, experimentation, evidence review, governance, and resource reconfiguration. It further identifies implications for owner-managers, support institutions, and future empirical research. The framework emphasizes that capability development should be proportionate to enterprise constraints and evaluated through decision quality, learning, resilience, and business outcomes rather than adoption indicators alone.